2023
DOI: 10.3390/su151813767
|View full text |Cite
|
Sign up to set email alerts
|

Activated Carbon Electrodes for Bioenergy Production in Microbial Fuel Cells Using Synthetic Wastewater as Substrate

Rickelmi Agüero-Quiñones,
Zairi Ávila-Sánchez,
Segundo Rojas-Flores
et al.

Abstract: The growing global energy demand drives the need to develop new clean energy technologies. In this context, microbial fuel cells (MFC) are one of the emerging technologies with great potential for eco-friendly energy generation; however, the correct choice of electrode material is a significant limitation in the optimal configuration of MFCs. Therefore, this research evaluated the efficiency of activated carbon (AC) anode electrodes for bioenergy production in MFC using synthetic wastewater as a substrate. Pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Figure 2a shows the voltage values obtained from the MFC-SC during the 12 days of monitoring, observing an increase in the values from the first day in the MFC-SC of the Target (0.08 V) and cell with P. stutzeri (0.12 V) until the sixth, where they reached their maximum values of 0.35 and 0.91 V, respectively, and then observed a decrease in values until the last day (0.17 and 0.15 V). The literature has reported that the increase in voltage values in the first few days is due to the oxidation-reduction process between the chambers due to a large amount of organic matter [27,28]. In contrast, the decrease in potential values is inevitable because the metabolism of the microorganisms is obtained through the oxidation of the substrate used, which is depleted [29,30].…”
Section: Results and Analysismentioning
confidence: 99%
“…Figure 2a shows the voltage values obtained from the MFC-SC during the 12 days of monitoring, observing an increase in the values from the first day in the MFC-SC of the Target (0.08 V) and cell with P. stutzeri (0.12 V) until the sixth, where they reached their maximum values of 0.35 and 0.91 V, respectively, and then observed a decrease in values until the last day (0.17 and 0.15 V). The literature has reported that the increase in voltage values in the first few days is due to the oxidation-reduction process between the chambers due to a large amount of organic matter [27,28]. In contrast, the decrease in potential values is inevitable because the metabolism of the microorganisms is obtained through the oxidation of the substrate used, which is depleted [29,30].…”
Section: Results and Analysismentioning
confidence: 99%
“…Furthermore, a large surface area of the biofilm generates the electrons produced from the reactions within the biofilms, which are transferred directly to the anodic electrode, avoiding the loss of electrons in the anodic solution [56]. Aguero et al ( 2023) reported a maximum ORP of 378 mV in their single-chamber MFCs using wastewater waste, where they mention that oxidizing environments facilitate electroactive microbes to grow favorably, leading to an increase in generated electrons, favoring the increase in the values of the electric current [57]. The substrates whose ORP values exceed 100 mV should be considered anaerobic environments; on the other hand, ORP values that are less than 100 mV should be considered aerobic due to the conditions in which microbes must metabolize to produce electrons [58].…”
Section: Results and Analysismentioning
confidence: 99%
“…In contrast, the anodic carbon electrode was centrally positioned within the MFC, covering an area of 200 cm 2 . The manufacturing process for the anodic electrode followed the method described by Agüero et al (2023) [6], as illustrated in Figure 1a. Internally, the electrodes were connected using Nafion 117 (Wilmington, NC, USA), and externally, they were linked via a resistor with a resistance value of 50 ± 3.4 Ω.…”
Section: Manufacturing Of Mfcsmentioning
confidence: 99%
“…The costs generated for the management and disposal of agricultural waste were reduced if they were used to generate another secondary good or if value was added to these types of waste [4,5]. Countries and companies dedicated to agribusiness have a significant problem due to the waste generated by producing different vegetables and fruits, contaminating and not taking advantage of these byproducts [6]. It is estimated that this production produces about 1.300 million tons of waste in one year, which has increased global pollution; it has been reported that 21% of greenhouse gases come from the agricultural sector [7,8].…”
Section: Introductionmentioning
confidence: 99%